Effects of 5-ethyl-1-phenyl-2-(1H) pyridone on serum biomarkers of multiorgan dysfunction and mortality in lipopolysaccharide/galactosamine and cecal ligation and puncture models of septic shock in mice - Grattendick, Ken J; Nakashima, James M; Giri, Shri N (Research communications in molecular pathology and pharmacology, 2009)
Septic shock results from a systemic host response to infection, in particular, and is associated with multiorgan dysfunction (MOD). Effective preventive measures against organ failure are essential as it is the cumulative burden of MOD that invariably leads to death. The aim of this study was to determine if a novel compound, 5-ethyl-1-phenyl-2-(1H) pyridone (5-EPP), could decrease the increased serum levels of various biomarkers of MOD in LPS/D-Galactosamine (LPS/D-GalN) and cecal ligation and puncture (CLP) models of septic shock in mice. Treatment with 5-EPP minimized the liver dysfunction as assessed by its ability to decrease the increased serum levels of aminotransferases. It also reduced proinflammatory cytokines such as TNF-alpha, IL-6 and IL-12, and offered complete protection against mortality in LPS/D-GalN model. 5-EPP treatment also offered a significant protection against LPS alone- induced mortality. Pretreatment with 5-EPP minimized the kidney, heart and muscle damage as assessed by its ability to decrease the CLP-induced increases in the serum levels of blood urea nitrogen, creatine kinase, glucose and mortality. Several possible mechanisms for the beneficial effects of 5-EPP in the LPS/D-GalN, LPS alone, and CLP models of septic shock have been discussed. It was concluded from the findings of this study that 5-EPP, a novel pyridone, is a promising candidate for the management of septic shock by offering protection against MOD and mortality clinically seen in septic patients.